Theorising worker–client relations in front‐line service work: Understanding the experience of non‐professionally affiliated workers in UK mental health services. (1st September 2021) - Procter, Stephen; Harrison, Deborah; Pearson, Pauline; Dickinson, Claire
Abstract: This paper contributes to a deeper understanding of front‐line service workers' experience of the worker–client relationship. It is based on a series of in‐depth interviews with non‐professionally affiliated workers in new front‐line roles in UK mental health services. The findings cover three main areas: worker motivation and orientation; the nature of the worker–client relationship; and the role played in the relationship by the structure of work and relationships with colleagues. Evidence is found to support the use of the framework of Korczynski ( Sociology, 43, 2009), but the research also suggests ways in which each of the framework's elements might be developed. It is argued that the idea of 'caring' is in need of refinement; that worker–client relations should not be seen solely in terms of client sovereignty and that a focus on the technical organisation of work can only go some way towards providing an understanding of the worker experience.